2022
DOI: 10.3390/en15093407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar on Biointensive Horticultural Crops and Its Economic Viability in the Mediterranean Climate

Francisco Miguel González-Pernas,
Cristina Grajera-Antolín,
Olivia García-Cámara
et al.

Abstract: The effects of biochar on different horticultural crops (lettuce, tomato, sweet pepper, and radish) were evaluated in the Mediterranean climate. Biochar was produced by pyrolysis of Pinus pinaster wood chips at 550 °C and used at 1 (B1) and 2 (B2) kg/m2 application rates on six 3.5 m2 plots in each treatment, with two control plots (B0). No fertilizer was used. Treatment B1 led to a significant increase (p < 0.01) of 35.4%, 98.1%, 28.4%, and 35.2% in the mean fresh weight of radishes, lettuce, tomatoes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Zhang et al (2013) showed that the application of biochar in paddy soil could bring economic benefits of 1.5 × 10 3 $ ha −1 without considering the cost of biochar. In general, because the advantages of carbon sequestration may cover some of the cost of biochar (González-Pernas et al, 2022), we propose that government subsidy programs and market mechanisms be implemented to incentivize farmers to use biochar (Xia et al, 2023).…”
Section: Net Ecosystem Economic Benefitsmentioning
confidence: 99%
“…Zhang et al (2013) showed that the application of biochar in paddy soil could bring economic benefits of 1.5 × 10 3 $ ha −1 without considering the cost of biochar. In general, because the advantages of carbon sequestration may cover some of the cost of biochar (González-Pernas et al, 2022), we propose that government subsidy programs and market mechanisms be implemented to incentivize farmers to use biochar (Xia et al, 2023).…”
Section: Net Ecosystem Economic Benefitsmentioning
confidence: 99%
“…Biochar contributes to building a refractory SOC pool and positively impacts SOC dynamics. Depending on management practices, agriculture can act as a net source/sink for GHGs [9]. Agricultural management practices that can foster soil C sequestration help mitigate climate change.…”
Section: Climate Change Mitigationmentioning
confidence: 99%
“…For the computation of income from crop improvement, the average price received by farmers for lettuce is considered to be 269.9 EUR/t (equivalent to 0.2699 EUR/kg) [9]. Considering 80,000 plants (www.starkeayres.co.za, accessed on 3 January 2023) per hectare and assuming that the improvement in yield is equivalent to the increase in mean fresh weight of lettuce plant, different benefits for each application rate were determined (see Supplementary Table S1).…”
Section: Economic Feasibilitymentioning
confidence: 99%
“…However, in recent years, environmental awareness in highly developed countries has increased, leading to an increase in the consumption of responsibly cultivated food from sustainably cultivated and organic crops [2][3][4]. Hence, an increasing number of studies are focusing on improving production in an environmentally friendly manner [4], particularly those examining the use of biochar for improving soil quality and crop yield [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of biochar application observed by other researchers indicate that biochar improves soils by increasing the pH, water and nutrient retention, and cation exchange capacity (CEC) and by enhancing the soil structure and biota [35][36][37], thereby improving plant growth [5][6][7][8]. The effect of biochar application in agricultural environments has been widely studied, reporting particularly good results for horticultural crops [10,[38][39][40][41]. Some authors have reported an improvement in corn yields from amending the soil with biochar [42][43][44].…”
Section: Introductionmentioning
confidence: 99%